Senegal - Nutrition Enhancement Program (NEP) First Phase - Mohan, P. C. (World Bank, Washington, DC, 2012)
Findings Info briefs reports on Good Practice in ongoing operational, economic and sector work carried out by the World Bank and its member governments in the Africa Region. This issue looks at the Senegal: Nutrition Enhancement Program (NEP), first phase which was the first nutrition project in Sub-Saharan Africa to use the Adaptable Program Lending (APL) instrument for the design of the program. The three project components were (i) Community Nutrition and Growth Promotion; (ii) Capacity Building and Monitoring and Evaluation and (iii) Program Management. Project interventions were conducted in the 3 poorest rural regions of Senegal, and in 34 Health Districts selected on the basis of social indicators. This info brief reports on the project impacts as well as lessons learned.